P12: PREDICTORS OF CONVERSION FROM MINIMALLY INVASIVE TO OPEN ADRENALECTOMY: A SYSTEMATIC REVIEW & META-ANALYSIS OF OBSERVATIONAL STUDIES. (27th April 2021) - Cagney, D; O'Leary, DP; Razzaq, Z; Majeed, M; Redmond, HP
Abstract: Introduction: Minimally invasive adrenalectomy has become the standard of care internationally in benign adrenal disease. Intra-operative conversion to open surgery is associated with significantly increased morbidity and prolonged hospital stay. The aim of this systematic review is to identify risk factors associated with intra-operative conversion of minimally invasive adrenalectomy. Method: This systematic review was conducted according to MOOSE guidelines. PubMed, EMBASE and Cochrane library were systematically searched for observational studies evaluating risk factors for intra-operative conversion of minimally invasive adrenalectomy to open surgery. Specific risk factors of interest included patient demographics, patient co-morbidities, tumour characteristics and histology. Result: Eight studies met the inclusion criteria for analysis with a total of 2939 patients. 6.02% (n=177) required intra-operative conversion. 67.5% (n=1983) underwent laparoscopic transperitoneal adrenalectomy. There were no significant associations between any patient demographics or co-morbidities and intra-operative conversion. Tumour characteristics such as right sided tumours (pooled odds ratio (OR), 1.51; 95% Confidence Interval (CI), 0.98-2.32; p=0.06) and increasing tumour size (OR, 2.29; 95% CI, 1.4-3.74; p=0.001) were shown to be significantly associated with an increased risk of conversion. Pheochromocytoma (OR, 2.21; 95% CI, 1.89-2.58; p<0.0001) and malignancy (OR, 5.38; 95% CI, 2.1-13.81; p=0.005) were also significant predictors of intra-operative conversion. Conclusion: Minimally invasive adrenalectomy has significantly reduced post-operative morbidity in patients requiring adrenal surgery but the need for intra-operative conversion remains significant. Identifying patients at increased risk of conversion pre-operatively may assist intra-operative decision making and contribute to improved patient outcomes. Take-home message: Minimally invasive adrenalectomy carries a significant risk of conversion. Recognising patients with known risk factors for conversion aids risk stratification and may contribute to better outcomes.